2017
DOI: 10.1590/1678-4766e2017042
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of insect galls in xeric and mesic habitats of Floresta Nacional de Silvânia, Brazil

Abstract: ABSTRACT. We investigated the insect gall distribution along savanna (xeric) and forest (mesic) vegetation in the Floresta Nacional de Silvânia, Goiás, Brazil. We tested if the insect gall diversity is higher in the xeric vegetation than in the mesic vegetation, as predicted by the hygrothermal stress hypothesis. The insect gall fauna was surveyed between December 2009 and June 2010 in two transects established each vegetation type. In total we found 186 insect gall morphotypes, distributed on 35 botanical fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Vegetation structure is sometimes more determinant than abiotic or anthropic effects (Kemp & Ellis, 2017) because they affect different insect groups and trophic levels (Obermaier et al, 2008). In this sense, there is evidence that environments with more complex vegetation may have a greater diversity of insects (Borges & Brown, 2001;Diniz et al, 2010), mainly herbivores (Leal et al, 2016;Bergamini et al, 2017). It is because more complex environments have greater habitat heterogeneity and thus greater resource availability (Grez & Gonzalez, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation structure is sometimes more determinant than abiotic or anthropic effects (Kemp & Ellis, 2017) because they affect different insect groups and trophic levels (Obermaier et al, 2008). In this sense, there is evidence that environments with more complex vegetation may have a greater diversity of insects (Borges & Brown, 2001;Diniz et al, 2010), mainly herbivores (Leal et al, 2016;Bergamini et al, 2017). It is because more complex environments have greater habitat heterogeneity and thus greater resource availability (Grez & Gonzalez, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Sessile and host-specific herbivores, such as gall-inducing insects, are usually patchily distributed within the populations of their host plants, and it has been suggested that both bottom-up and top-down effects explain variations in gall abundance (Araújo et al 2006, Barbosa & Fernandes 2014, distribution (Lara et al 2008;Bergamini et al 2017) and survivorship (Hosaka et al 2009). Given the specific features of insect-plant interactions, a number of hypotheses have been proposed to account for the patterns of distribution and abundance of gall morphotypes, and of insects that induce these galls on their respective plant hosts (Fleck & Fonseca 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The event was noticed on December 8th, at 8:30 pm during a routine inspection of a mist net installed in a fragment of semi-deciduous forest (16° 38' 25.29" S; 48° 38' 57.24" W) at the Silvânia National Forest Conservation Unit (FLONA-Silvânia), Silvânia, Goiás, Brazil. The Park has an area of 486.37 ha (MMA 2021), exhibiting almost all types of Cerrado vegetation, but mainly savannas and typical forests (Araújo et al 2012;Bergamini et al 2017). The rodent was removed from the mist-net, weighed (64 g), and released in the same capture area (Figure 1).…”
mentioning
confidence: 99%